Answer:
(-8, 8)
Explanation:
Plug in the y from the top equation into the y of the bottom equation
x² + (x + 16)² = 128
x² + x² + 32x + 256 = 128
Subtract 128 from both sides to make it equal to zero
2x² + 32x + 256 = 128
- 128 - 128
2x² + 32x + 128 = 0
Divide both sides by 2
(2x² + 32x + 128)2 = 0/2
x² + 16x + 64 = 0
Factor the equation
(x + 8)(x + 8) = 0
We see that x will have to be -8 for it to equal zero
so x = -8
Plug the new x into one of the original equations; let's use the top one
y = -8 + 16
y = 8